EXCELLENT SERVICE AND PUBLIC RELATIONS STRATEGY OF PT. ACE HARDWARE IN THE ERA OF SOCIETY 5.0 - Sibagariang, Murni Juliasni; Andrini, Susi (Transpublika Publisher, 2022)
This study aims to explain how excellent service for the implementation of the Public Relations function and Public Relations Strategy is carried out by the ACE Hardware company to customers in the Society 5.0 era. The methodology used is descriptive qualitative. Kotler and Keller theory is used to analyze PR Strategy which has seven (7) concepts as indicators; a) publication, b) sponsorship, c) event, d) talk, e) news media, f) identity, g) social activities, while the analysis of Excellent Service is taken from the Rangkuti theory which has three (3) concepts as indicators; a) developing services, b) meeting expectations, c) maintaining and maintaining customers facing the Society 5.0 era, in this case using the Omni Channel (an application launched as a form of digital transformation in increasing the convenience of consumers in shopping and accessing ACE Hardware products). The importance of the role of digital content is also considered because the high level of use of social media makes people closer to the online world. Data collection was carried out through an in-depth interview process with other supporters from literature reviews, literature, books, journals, the internet or those relevant to this research. Data analysis was carried out using a coading process (open coading, axial coading and selective coading). The results of the study show that ACE Hardware Company has implemented a PR strategy based on the theory of PR strategy and excellent service, by maximizing the use of omni-channels in the era of Society 5.0.